Development and Evaluation of Vero Cell-Derived Master Donor Viruses for Influenza Pandemic Preparedness - Po-Ling Chen; Tsai-Teng Tzeng; Alan Yung-Chih Hu; Lily Hui-Ching Wang; Min-Shi Lee (Vaccines, 2020)
The embryonated egg-based platform currently produces the majority of seasonal influenza vaccines by employing a well-developed master donor virus (MDV, A/PR/8/34 (PR8)) to generate high-growth reassortants (HGRs) for A/H1N1 and A/H3N2 subtypes. Although the egg-based platform can supply enough seasonal influenza vaccines, it cannot meet surging demands during influenza pandemics. Therefore, multi-purpose platforms are desirable for pandemic preparedness. The Vero cell-based production platform is widely used for human vaccines and could be a potential multi-purpose platform for pandemic influenza vaccines. However, many wild-type and egg-derived influenza viruses cannot grow efficiently in Vero cells. Therefore, it is critical to develop Vero cell-derived high-growth MDVs for pandemic preparedness. In this study, we evaluated two in-house MDVs (Vero-15 and VB5) and two external MDVs (PR8 and PR8-HY) to generate Vero cell-derived HGRs for five avian influenza viruses (AIVs) with pandemic potentials (H5N1 clade 2.3.4, H5N1 clade 2.3.2.1, American-lineage H5N2, H7N9 first wave and H7N9 fifth wave). Overall, no single MDV could generate HGRs for all five AIVs, but this goal could be achieved by employing two in-house MDVs (vB5 and Vero-15). In immunization studies, mice received two doses of Vero cell-derived inactivated H5N1 and H7N9 whole virus antigens adjuvanted with alum and developed robust antibody responses.